Bleeding Rate for Ultrasound‐Guided Paracentesis in Thrombocytopenic Patients. (11th September 2015) - Kurup, A. Nicholas; Lekah, Alexander; Reardon, Scott T.; Schmit, Grant D.; McDonald, Jennifer S.; Carter, Rickey E.; Kamath, Patrick S.; Callstrom, Matthew R.; Atwell, Thomas D.
Abstract : Objectives: The purpose of this study was to determine the rate of major bleeding complications for ultrasound‐guided paracentesis performed in thrombocytopenic patients. Methods: We retrospectively reviewed the electronic medical records of patients with platelet counts of less than 50, 000/μL who had ultrasound‐guided paracenteses performed in the Department of Radiology without correcting preprocedural platelet transfusions between 2005 and 2011. Medical records were evaluated for evidence of major bleeding complications (grade 3 or higher as defined by the National Institutes of Health's Common Terminology Criteria for Adverse Events, version 4.03) and their clinical sequelae. Platelet count and bleeding complications were evaluated for an association, and a sensitivity analysis was performed to determine whether analysis of a control group of patients without thrombocytopenia would yield added confidence in this assessment. Results: Among 304 procedures in 205 thrombocytopenic patients (69% male; mean age ± SD, 56.6 ± 11.9 years), the mean platelet count was 38, 400 ± 9300/μL (range, 9000–49, 000/μL). Three major bleeding complications requiring red blood cell transfusion were observed in patients with platelet counts of 41, 000 to 46, 000/μL, for a complication rate of 0.99% (95% confidence interval, 0.3%–2.9%). No patient required an additional procedure or died because of the bleeding complication. There was no association of platelet count with bleeding complications. The sensitivity analysis showed that further evaluation of patients with normal platelet counts would not add to the conclusion. Conclusions: The risk of major bleeding after ultrasound‐guided paracentesis in thrombocytopenic patients is very low. In most patients, routine assessment of the preprocedural serum platelet concentration is not necessary, and correction of such an abnormal laboratory value is not indicated.